Legal Policy to Improve the Activities of Government Bodies and the Law Enforcement System Considerring the Specifics of the Territory Northern Region - AVDEEV, Vadim Avdeevich; ANISIMOV, Valery Filippovich; MOROZOV, Aleksey Vital'yevich; SHULYAK, Igor Mikhaylovich; KALLIMULIN, Tair Rustamovich (Journal of Environmental Management and Tourism, 2021)
The article explores the key directions to improve the effectiveness of legal policy on the management for small indigenous peoples in the context of globalization. The importance of the preservation and development of ethnic groups in the Northern regions is noted. The article investigates the issues of improving the legal tools for regulating public relations related to the indigenous peoples of the North. Close attention is paid to the importance of managing the indigenous small numbered peoples of the North taking into account state policy. An analysis is given for the characteristics of indigenous peoples and their different levels of economic, social and cultural development.